Modern condition of legislative and normative basis of securing ecological safety of avia¬tion transport - Запорожец, А. И.; Петрашевский, О. Л. (Proceedings of National Aviation University (archive), 1999)
Considered is the necessity of transition of the Ukrainian legislation and normative acts of environment condition regulation to the approaches of EEC. The given approaches will in the nearest future considerably influence the development of aviation transport